2019
DOI: 10.1186/s12917-019-1904-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fetal calf serum on propagation of duck hepatitis A virus genotype 3 in duck embryo fibroblast cells

Abstract: Background Duck viral hepatitis (DVH) is a highly contagious viral disease affecting ducks. It can be caused by five agents, including duck hepatitis A virus genotypes 1 (DHAV-1), 2 (DHAV-2), and 3 (DHAV-3), as well as duck hepatitis virus 2 and duck hepatitis virus 3. Since 2007, DHAV-3 has been known to be the most prevalent in East and South Asia. So far, the information regarding the propagation of DHAV-3 in cultured cells is limited. In this study, we describe the comparative studies on the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 42 publications
1
6
0
Order By: Relevance
“…Earlier work in our laboratory showed that the use of CS in maintenance medium is of help to the replication of DHAV-3 in DEF cells. Unlike DHAV-1, DHAV-3 cannot produce cytopathic changes in DEF cells [37]. Thus, the present observations further demonstrated that DHAV-1 and DHAV-3 infections lead to disparate effects on DEF cells.…”
Section: Discussionsupporting
confidence: 67%
See 4 more Smart Citations
“…Earlier work in our laboratory showed that the use of CS in maintenance medium is of help to the replication of DHAV-3 in DEF cells. Unlike DHAV-1, DHAV-3 cannot produce cytopathic changes in DEF cells [37]. Thus, the present observations further demonstrated that DHAV-1 and DHAV-3 infections lead to disparate effects on DEF cells.…”
Section: Discussionsupporting
confidence: 67%
“…At present, it is uncertain whether the effect of FCS on virus loads in supernatant is associated with FCS-mediated inhibitory impact on virus assembly and release. A recent work in our laboratory showed that FCS exerts an inhibitory effect on DHAV-3 through the same mechanisms [37], suggesting that an FCS-mediated inhibitory effect on DHAV replication in cell cultures shows no genotype specificity. Collectively, these data provide a promising strategy for the development of a potent inhibitor against DHAV by further biochemical analysis of FCS.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations